Potential of using the diversity indexs of earthworms to evaluate the quality of vegetable farmland in Da Nang city - Khanh, Nguyen Van; Minh, Vo Van; Hong Ha, Pham Thi; Phuong Anh, Vu Thi; Thuy An, Ngo Thi (Academia Journal of Biology, 2012)
Using earthworms to evaluate the quality of agricultural land has been reasearched widely in many countries. Currently, agricultural land pollution, has been occurring in many regions of Da Nang city, due to over-fertilization, pesticide overuse and wastes discharged from industrial zones. In recent decades, earthworm has been used as a bio-indicator in support to soil physical and chemical methods and considered highly effective in monitoring of the quality of soil environment. The research results showed that there were 14 species and 5 genera in three investigated sites, the diversity indexes were low (< 1). In general, correlation levels between biological indexes and physiochemical indexes ranged from weak to relatively significant. In particular, earthworm biomass index correlated from medium to relatively significant levels with total phosphorus percentage and organic matter percentage, respectively. It could be noticed that earthworm biomass could be used as a bio-parameter in evaluating the concentrations of total phosphorus and organic matter in farmland.